PEMANFAATAN RUANG TERBUKA SCIENCE PARK (TAMAN ILMU) UNIVERSITAS RIAU BAGI MASYARAKAT SEKITARNYA - Mariska, Mia; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research to do in the Open Space Science Park, University of Riau Jl. HR. Soebrantas Kampus Bina Widya Km. 12.5 Simpang Baru, Pekanbaru. The purpose of this study was to determine the activity of a visitor as well as the reasons people choose to visit the Science Park, University of Riau. The method used in this research is descriptive quantitative. Intake of research subjects used was accidental sampling. Samples taken in this study amounted to 81 people. Therefore, the author will develop the concept, gathered data in the study area. Data collection techniques used were questionnaires, interviews and observation. As for the data processing techniques using means editing, coding and tabulation. Then to menganilisisnya will be collected and grouped according to their respective groups, and then processed using SPSS application and described in the form of tables and conclusion along with suggestions. Based on the implementation of the research results, visitors who come to visit to perform various activities such as recreational activities, education and economy. Visitors also utilize the facilities and existing facilities such as a lake, rides and shade trees along with seating around it. Regional Science Park, University of Riau was used as an alternative destination by the visitors, it is diebabkan by the lack of neighborhood open space natural shades Area Pekanbaru city, especially in the Panam district Handsome districts. The few things that background for why visitors choose a goal of his visit in the Science Park, University of Riau is as reasons: park atmosphere is cool, shady and leafy, the location is easily accessible, the availability of various facilities and adequate facilities, the level of comfort and safety a satisfactory and cost-effective. It can be concluded that the process of social exchange in the region. This is evidenced by the many visitors who come repeatedly.Keywords: The utilization of open space Science Park University of Riau, visitor activity, and reason for visit